Oil and Gas Conference. Day 2. Tape 05. - Memorial University of Newfoundland. Extension Service (MUN Extension Service, 1979)
Speech by Cabot Martin (philosophical assumptions on which oil and gas regulations are based, changes which must be made); Questions. Video begins with very brief excerpt of separate video with question to Ian Clarke.